High‐Performance Ammonium Cobalt Phosphate Nanosheet Electrocatalyst for Alkaline Saline Water Oxidation - Zhongxin Song; Kaixi (Cathy) Wang; Qian Sun; Lei Zhang; Junjie Li; Dingjiu Li; Pok‐Wai Sze; Yue Liang; Xueliang Sun; Xian‐Zhu Fu; Jing‐Li Luo (Advanced Science, 2021)
Abstract The development of highly efficient electrocatalysts toward the oxygen evolution reaction is imperative for advancing water splitting technology to generate clean hydrogen energy. Herein, a two dimensional (2D) nanosheet ammonium cobalt phosphate hydrate (NH4CoPO4·H2O) catalyst based on the earth‐abundant non‐noble metal is reported. When used for the challenging alkaline saline water electrolysis, the NH4CoPO4·H2O catalyst with the optimal thickness of 30 nm achieves current densities of 10 and 100 mA cm−2 at the record low overpotentials of 252 and 268 mV, respectively, while maintaining remarkable stability during the alkaline saline water oxidation at room temperature. X‐ray absorption fine spectra reveal that the activation of Co (II) ions (in NH4CoPO4·H2O) to Co (III) species constructs the electrocatalytic active sites. The 2D nanosheet morphology of NH4CoPO4·H2O provides a larger active surface area and more surface‐exposed active sites, which enable the nanosheet catalyst to facilitate the alkaline freshwater and simulated seawater oxidation with excellent activity. The facile and environmentally‐benign H2O‐mediated synthesis route under mild condition makes NH4CoPO4·H2O catalyst highly feasible for practical manufacturing. In comparison with noble metals, this novel electrocatalyst offers a cost‐effective alternative for economic saline water oxidation to advance water electrolysis technology.